Television Sitcoms through the Decades: Transmedia Intertextuality in Marvel’s WandaVision - Isadora García-Avis; Tomás Atarama-Rojas (Communication & Society (Formerly Comunicación y Sociedad))
In the current era of cultural convergence, the audiovisual production ecosystem is defined, among other things, by the growth of streaming platforms and the rise of transmedia storytelling. In this context, WandaVision (Schaeffer, 2021) stands out as a TV miniseries produced for a streaming platform (Disney+) that relies on transmedia intertextuality not only to expand its narrative, but also to deepen its storyworld.